Instrumentalized migration: avoiding the trap [version 2; peer review: 1 approved, 3 approved with reservations, 1 not approved] - Beth James; Hanne Dumur-Laanila; Annabel Miller; Josip Mandić; Gordan Akrap; Maxime Lebrun; Sophie Bujold; Tanja Ellingsen (Open Research Europe)
The article considers the European Union’s (EU) and its Member States’ capacities to face the challenge posed by instrumentalized migration as a hybrid threat activity. Instrumentalized migration in this context entails people being forcibly displaced towards an EU border and made to cross it to claim international protection with an aim of causing capacity overload, adverse reactions, or exerting larger pressure on the target state. Because global migration is a highly politicised and securitized issue in European and domestic politics, authoritarian states may see a strategic opportunity in instrumentalizing it their advantage. Responding strategically to instrumentalized migration requires identifying policy pitfalls and value traps while managing to maintain as many tools and as much space for manoeuvre as possible. Authoritarian states may use instrumentalized migration to further their wider agenda of turning international law into a system of rules which would primarily protect state sovereignty and non-interference at the expense of the international protection of human rights. Responses to instrumentalized migration have impacts and establish precedence in terms of acceptable state practice. Considering this, this article discusses the EU’s new Pact on Migration and Asylum and examines how it can be used to the advantage of Member States when dealing with instances of instrumentalized migration.